A One Health assessment of antimicrobial-resistant Enterobacterales in migratory little stints (Calidris minuta) and aquatic ecosystems in the Kenyan Rift Valley - Catherine W. Mbuthia; Rael J. Too; Alexanda Mzula; Titus S. Imboma; John Kiiru; Samuel Kariuki; Abubakar S. Hoza (PLoS ONE, 2026)
Palearctic migratory little stints ( Calidris minuta ) can acquire resistant bacteria from contaminated environments and facilitate their transboundary spread. This two-year repeated cross-sectional study assessed the frequency and distribution of multidrug-resistant (MDR) and extended-spectrum beta-lactamase (ESBL)-producing Enterobacterales. Isolates were recovered from fecal samples of C. minuta foraging at the shores of Lakes Bogoria (low anthropogenic activities) and Magadi (high anthropogenic activities), as well as from peripheral freshwater sources shared by birds, humans, livestock and wildlife. A total of 184 fecal samples and 48 water samples were collected upon the birds’ arrival from the Arctic (cohort 1) and pre-departure from the Rift Valley lakes (cohort 2). Samples were cultured, bacterial isolates were identified using MALDI-TOF MS platform and tested against 12 antimicrobials using the Kirby-Bauer disk method. Of the 294 isolates (16 genera and 33 species), Enterobacter spp (31.0%, n = 91) and Escherichia coli (17.3%, n = 51) predominated. Resistance was highest for ampicillin (50%) and lowest for meropenem (1.0%). The predominant MDR phenotype was a combination of resistances to ampicillin, tetracycline, and sulfamethoxazole-trimethoprim. Specifically, 38 (12.9%) isolates were MDR, 37 (12.6%) co-expressed ESBL-MDR traits, and 19 (6.5%) were ESBL producers that did not meet MDR criteria. Enterobacter spp showed the highest frequencies of MDR (8.2%, n = 24) and combined ESBL-MDR (4.8%, n = 14) phenotypes, while Acinetobacter spp (3.4%, n = 10) were the most frequent ESBL producers. The statistically non-significant differences (p > 0.05) across study areas, sample sources, and cohorts suggest that resistant strains are pervasive throughout these landscapes, irrespective of anthropogenic pressures. This is the first study to link C. minuta to the antimicrobial resistance (AMR) epidemiological circuit. Our findings underscore the need to include migratory wild birds in AMR surveillance and utilizing whole-genome sequencing to accurately trace the origin and dissemination pathways of AMR strains.